Treatment of Manovikaras in Ayurveda - T., Dr. Dhanya (International Journal of Innovative Research in Medical Science, 2017)
This review article deals with Chikitsa told in Ayurveda for Mano Vikaras (mental disorders). Ayurveda has always laid special emphasis on maintaining and promoting health and preventing disease rather than curing disease. In modern science continuous and prolonged use of sedatives, tranquilizers, anxiolytics and hypnotics for treating various mental ailments resulted in rebound phenomenon and drug dependence causing further frustration and decline in mental status. In Ayurveda Chikitsa is classified into 3 types Daivavyapashraya Chikitsa (divine therapy), Yuktivyapashraya Chikitsa (rational therapy) and Satvavajaya Chikitsa (psychotherapy). Daivavyapashraya Chikitsa involvesmeasures to combat Daivakrit diseases. Yuktivyapasraya is treatment based on fundamental principles of Ayurveda. Sattvavajaya Chikitsa is to control the mind by withdrawing it from undesired objects. Ayurveda gives more stress to Sattvvajaya Chikitsa and Daivavyapashraya Chikitsa in managing manovikaras. There is increasing need of Sattvavajaya Chikitsa in examining a patient and treating disease. This article will help readers to understand role of Ayurveda in maintaining Manasika Swasthyam